The Ugandan Youth Quality of Life index: assessing the relevance of incorporating perceived importance into the quality of life measure and factors associated with the quality of life among youth in slum areas of Kampala, Uganda. Issue 1 (1st December 2016) - Renzaho, Andre M. N.; Kamara, Joseph Kihika; Kamanga, Gilbert
Abstract : Background: While quality of life (QoL) has long been an explicit policy goal for international development programmes, no instruments have specifically been developed for measuring health-related QoL in resource-limited settings. The aim of this study was to develop and validate a QoL instrument for use in international aid and development programmes and to assess factors associated with QoL among youth participating in a civic engagement project in Kampala. Design: Using systematic random sampling, data were collected on 663 participants aged between 13 and 24 years in Kampala. The QoL questionnaire included 36 questions divided into a two-part scale: 18 questions rated for satisfaction (Part 1) and 18 other questions rated on importance (Part 2). The total sample was randomly divided into two split-half samples: one for the exploratory factor analysis (EFA; N =310) and the other for the confirmatorty factor analysis (CFA; N =353). The effect of demographic, socio-economic, and lifestyle factors on QoL was assessed using linear regressions. Results: The EFA yielded three factors: living conditions and lifestyle (seven items, α =0.84), social relationships (five items, α =0.86), and personal independence (five items, α =0.76). In the CFA, the initial model demonstrated a poor to marginal fit model. Its re-specification by examining modification indices resulted in a good model fit: Comparative Fit Index=0.95, Root Mean Square Error of Approximation=0.06, and p of Close Fit >0.05. The model incorporating perceived importance had lower Akaike Information Criteria and Bayesian Information Criteria values than the unweighted model, thereby providing very strong support to weight satisfaction scores with importance ratings when measuring QoL in Uganda. Poor QoL was associated with poor educational attainment, drug and substance misuse, and family disruption. Conclusions: The findings suggest that there is a relationship between QoL and lifestyle and structural issues among youth in Uganda. The study provides the first validated QoL measure to allow government and non-government organisations in low- and middle-income countries to track progress of international aid and development programmes.